THU0707-HPR FOLLOW-UP CARE FOR PATIENTS WITH ESTABLISHED INFLAMMATORY JOINT DISEASES – A FOCUS GROUP STUDY ON PATIENTS' EXPERIENCES FROM REFRAIMING THE ORGANIZATIONAL SUPPORT FOR INCREASED PATIENT INVOLVEMENT. (June 2019) - Bech, Bianca; Lykkegaard, Jens Jørgen; Lundbak, Tine; Birkeland, Line Mette; Schlyter, Mette Lund; Hansen, Lotte Hanne; Dalsgaard, Lillian; Esbensen, Bente Appel
Abstract : Background: Internationally, a Treat-to-Target strategy for proactive management of inflammatory joint diseases (IJD) is recommended. 1, 2 This includes continuous monitoring of the arthritis, which covers symptoms and the significance of the disease for everyday life. 2, 3 Control of disease activity has traditionally been ensured with fixed outpatient visits to rheumatologists. 4 However, in general there is a growing interest to involve patients in the control and treatment of their own disease. Open Assess in our outpatient clinic was implemented during October 2016 to respond to fluctuating needs among the patients with established IJD. Patient participation in Open Assess were primarily patient-initiated. They were expected to respond to symptoms and other disease-, and treatment-related needs. In addition, two half-yearly planned visits were offered patients: 1) An a nnual traditional medical consultation with a rheumatologist, and 2) A new Annual c onsultation with an experienced registered rheumatology nurse (RRN) . Objectives: To explore how people with established IJD in stable phase, experience Open-Access as a way to involve patients in their own disease and treatment. Methods: We conducted a qualitative study based on four semi-structured focus group interviews among patients with established inflammatory joint disease (Rheumatoid arthritis (RA), axial spondyloarthritis (axSpA) and psoriasis arthritis (PsA)) participating in the Open Access set-up. The analysis of the transcribed interviews was based on content analysis. A patient research partner was involved in all phases of the study. Results: In total 25 patients with IJD participated (20 female (80%), mean age 61.8 (range 28-79)) with RA (n=20), PsA (n=3), axSpA (n=1) and polyarthritis (n=1) participated. We identified three themes. Changes in follow-up care do not affect patients' perceived support in disease control, referring to patient's perception of more time available to both themselves and health professionals, as well as trust in access to professional support whenever needed. Adequate information to act within a new patient role, reflecting patients' uncertainty in the transition to Open Access combined with confusion about distribution of responsibilities in the new set-up. Arthritis in a broader perspective, expanding patients understanding of their illness by interaction over time with both a rheumatologist and a rheumatology nurse in a focused dialogue to involve the patient in managing their own health. Conclusion: Patients following Open-Access welcome the flexibility and involvement in disease control. However, patients need relevant information to be able to act adequately to the new patient role. Interacting with both rheumatologists and nurses, combined with sufficient time for dialogue, broaden patients' perspective, make opportunities for action visible, and contribute to patient's ability to participate in the managing of their own condition. References: [1] Smolen JS, et al. Treating spondyloarthritis, including ankylosing spondylitis and psoriatic arthritis, to target: recommendations of an international task force. Ann Rheum Dis 2014 [2] Smolen JS, et al. Treating rheumatoid arthritis to target: 2014 update of the recommendations of an international task force. Ann Rheum Dis 2016 [3] Bykerk VP, et al. Flares in rheumatoid arthritis: frequency and management. A report from the BRASS registry. J Rheumatol 2014 [4] Combe B, et al. 2016 update of the EULAR recommendations for the management of early arthritis. Ann Rheum Dis 2017 Disclosure of Interests: Bianca Bech: None declared, Jens Jørgen Lykkegaard: None declared, Tine Lundbak: None declared, Line Mette Birkeland: None declared, Mette Lund Schlyter: None declared, Lotte Hanne Hansen : None declared, Lillian Dalsgaard: None declared, Bente Appel Esbensen Speakers bureau: For Pfizer